2019
DOI: 10.1242/jcs.230755
|View full text |Cite
|
Sign up to set email alerts
|

New quantitative approach reveals heterogeneity in mitochondrial structure–function relations in tumor-initiating cells

Abstract: Steady-state mitochondrial structure or morphology is primarily maintained by a balance of opposing fission and fusion events between individual mitochondria, which is collectively referred to as mitochondrial dynamics. The details of the bidirectional relationship between the status of mitochondrial dynamics (structure) and energetics (function) require methods to integrate these mitochondrial aspects. To study the quantitative relationship between the status of mitochondrial dynamics (fission, fusion, matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…In our earlier study, we showed that elevated Hipk increases glucose uptake and glycolytic flux ( Wong et al, 2019 ). Given that mitochondrial metabolism can be influenced by alterations in energy demand and nutrient supply ( Liesa and Shirihai, 2013 ; Spurlock et al, 2019 ), we were motivated to examine whether elevated Hipk leads to any changes in mitochondrial dynamics, abundance and energetics. We first examined mitochondrial morphology using mito-GFP ( Pilling et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our earlier study, we showed that elevated Hipk increases glucose uptake and glycolytic flux ( Wong et al, 2019 ). Given that mitochondrial metabolism can be influenced by alterations in energy demand and nutrient supply ( Liesa and Shirihai, 2013 ; Spurlock et al, 2019 ), we were motivated to examine whether elevated Hipk leads to any changes in mitochondrial dynamics, abundance and energetics. We first examined mitochondrial morphology using mito-GFP ( Pilling et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 D,D′). Several image analysis tools such as MitoGraph ( Viana et al, 2015 ), MiNA ( Valente et al, 2017 ) and Mito-SinCe 2 ( Spurlock et al, 2019 ) have been developed for quantifying mitochondrial dynamics. In this study, we used the MiNA (Mitochondrial Network Analysis) toolset to generate skeleton images for quantitative analyses of mitochondrial morphology ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic remodeling such as decreased oxidative phosphorylation in mitochondria and increased glycolysis in the cytoplasm (Warburg effect), is a hallmark of cancer [ 53 , 105 , 106 , 107 ]. Breast cancer cells can compensate energy deficits during impaired oxidative phosphorylation by upregulating genes involved in glycolysis [ 108 ].…”
Section: Alteration Of Mitochondrial Energy Metabolismmentioning
confidence: 99%
“…Mitochondrial activity is a critical determinant of primary HSCs with LT-hematopoietic reconstituting potential (Vannini et al, 2016;Anso et al, 2017;Spurlock et al, 2019;Liang et al, 2020). We previously demonstrated that VPA-expanded HSCs exhibited a remodeled primitive mitochondrial network characterized by low mitochondrial ROS, mass and MMP (Papa et al, 2018).…”
Section: Vpa-generated Hscs That Are Characterized By Increased Exprementioning
confidence: 99%
“…This LT-repopulating capacity is due to the HSC's ability to balance self-renewal with commitment decisions (Orkin and Zon, 2008;Seita and Weissman, 2010). Such balance is controlled by complex mechanisms that rely on both the transcriptomic and metabolic properties of LT-HSCs (Jang and Sharkis, 2007;Schieke et al, 2008;Takubo et al, 2013;Warr and Passegue, 2013;Kohli and Passegue, 2014;Maryanovich et al, 2015;Mohrin et al, 2015;Vannini et al, 2016;Anso et al, 2017;Papa et al, 2019b;Spurlock et al, 2019). The transcriptome and metabolism of LT-HSCs are intrinsically coupled to their mitochondrial activity, which is profoundly altered during HSC commitment and maturation.…”
Section: Introductionmentioning
confidence: 99%